2018
DOI: 10.3892/etm.2018.5982
|View full text |Cite
|
Sign up to set email alerts
|

Rho/Rho-associated protein kinase signaling pathway‑mediated downregulation of runt-related transcription factor 2 expression promotes the differentiation of dental pulp stem cells into odontoblasts

Abstract: The present study investigated the role of runt-related transcription factor 2 (Runx2) in regulating the differentiation of human dental pulp stem cells (hDPSCs) into odontoblasts under the mediation of the Rho/Rho-associated protein kinase (ROCK) signaling pathway. hDPSCs and human bone marrow mesenchymal stem cells (hBMSCs) were mineralized to induce differentiation. The expression levels of odontoblast- and osteoblast-specific proteins, dentin sialophosphoprotein (DSPP), osteocalcin (OCN) and Runx2, were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…61 reported that the pattern of RUNX2 expression fluctuated during osteogenic differentiation of MSCs. The expression of RUNX2 was found to increase initially and then to decrease in human dental pulp MSCs, while it remained consistently high in human bone marrow MSCs during their osteogenic/odontogenic differentiation 61 . It was also reported that the mRNA level of RUNX2 correlate positively with the level of OCN during osteogenesis 62 .…”
Section: Discussionmentioning
confidence: 99%
“…61 reported that the pattern of RUNX2 expression fluctuated during osteogenic differentiation of MSCs. The expression of RUNX2 was found to increase initially and then to decrease in human dental pulp MSCs, while it remained consistently high in human bone marrow MSCs during their osteogenic/odontogenic differentiation 61 . It was also reported that the mRNA level of RUNX2 correlate positively with the level of OCN during osteogenesis 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the expression of Runx2 , an essential transcriptional factor for the differentiation and maturation of osteoblasts [ 29 ], is constantly increasing during the differentiation of osteoblasts, the expression of Runx2 is known to exhibit a stage-specific expression level of Runx2 during the differentiation of odontoblast; the increased expression of Runx2 in the early stage is suppressed in the terminal stage associated with the enhanced expression of DSPP [ 30 , 31 ], suggesting that inhibition of PI3-AKT-mTOR signal pathway might accelerate the ability of osteogenic/dentinogenic differentiation of SCAP. Recent studies clarified that stage-specific regulation of the Runx2-targeting molecules, including microRNA 338-3p, microtubule-associated protein tau, small heterodimer partner, and Rho/Rho-associated protein kinase, transcriptionally suppresses Runx2 expression, resulting in DSPP upregulation at the terminal stage of odontoblast differentiation [ 32 35 ]. Current studies report that AKT and its underlying signal FOXO1 negatively regulate Runx2 transcription in osteosarcoma and prostate cancer cells [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the cytoskeleton and the Rho/ROCK pathway of MSCs on rope-like silk scaffolds diminish the expression of tendon differentiation markers and lead to a loss of spindle morphology ( Maharam et al, 2015 ). Furthermore, downregulation of osteogenic marker RUNX2, mediated via the Rho/ROCK signaling pathway promotes the differentiation of dental pulp stem cells into odontoblasts ( Huang et al, 2018 ). Rho and the actin cytoskeleton have also been shown to be necessary to maintain nuclear YAP/TAZ in MSCs ( Dupont et al, 2011 ).…”
Section: Mechanobiology: Mechanosensation and Mechanotransductionmentioning
confidence: 99%